A deadly cocktail? The fusion of Europe and immigration in the UK press. Issue 3 (27th May 2017) - Balch, Alex; Balabanova, Ekaterina
ABSTRACT: This article asks how the EU is imagined and deployed in different justifications for national restrictions on the free movement of European citizens. It does this by analysing press coverage in the UK, where concerns about the issues of immigration and European integration contributed to a victory for 'Brexit' in the 2016 referendum. It develops a novel technique for analysing the political dimension of media debates offering a conceptual map to navigate the confusing fusion of Euroscepticism and anti-immigrationism. Through reference to political theories on immigration controls, and ideas about European integration from EU studies a series of hypothetical roles and functions for the EU are developed. These are then used as a framework to analyse coverage in the UK national media in two crucial time-periods: 2006 and 2013. The article's findings challenge conventional wisdom that Euroscepticism and anti-immigrationism are (a) closely correlated and (b) map neatly onto existing left-right political preferences. The results show that the left-right dimension was less salient in 2013 than in 2006, the space within which discussions of the EU take place narrowed, and the economic and political aspects of regional integration were increasingly overshadowed by the image of the EU as supranational entity.